Multiple spawning of the red swamp crayfish Procambarus clarkii (Decapoda: Cambaridae) under laboratory conditions - Hamasaki, Katsuyuki; Nishimoto, Sota; Dan, Shigeki (Invertebrate reproduction & development, 2022)
A season-independent juvenile supply system is required for developing the aquaculture of the red swamp crayfish Procambarus clarkii. The present study aimed to test if P. clarkii females can spawn multiple times under a constant temperature (25°C) and photoperiod (14 L: 10D) - conditions that are suitable for their reproduction. When a female developed glair glands on the underside of its uropods, it was paired with a single male for mating. Females that laid the first egg batch from the middle of July to the end of October were successively cultured; large proportions of individuals then rematured (76%) and laid a second egg batch (94%) from late September to early February. Although we finished the culture experiments in early February when all the test females had laid their second egg batch, a third spawning occurred in 27% of these females. Overall, the earlier the females spawned, the more egg batches they laid. Fecundity was correlated with female body size (postorbital carapace length) and decreased in accordance with spawning time. The egg development rate was very low in some females - probably depending on male fertility. We highlight future research subjects for developing a continuous breeding system in P. clarkii.